2022
DOI: 10.1038/s41467-022-30498-y
|View full text |Cite
|
Sign up to set email alerts
|

On-chip integrated process-programmable sub-10 nm thick molecular devices switching between photomultiplication and memristive behaviour

Abstract: Molecular devices constructed by sub-10 nm thick molecular layers are promising candidates for a new generation of integratable nanoelectronic applications. Here, we report integrated molecular devices based on ultrathin copper phthalocyanine/fullerene hybrid layers with microtubular soft-contacts, which exhibit process-programmable functionality switching between photomultiplication and memristive behaviour. The local electric field at the interface between the polymer bottom electrode and the enclosed molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…After that, Li et al further developed fully integrated process-programmable molecular devices by using a polymeric bottom electrode as the "ion reservoir" and rolled-up metallic nanomembranes as the "soft contact." [300] As demonstrated in Figure 14H [281] Copyright 2010, American Chemical Society. B) Schematic and SEM image of outer rolled-up soft contact.…”
Section: Rolled-up Soft Contactmentioning
confidence: 96%
“…After that, Li et al further developed fully integrated process-programmable molecular devices by using a polymeric bottom electrode as the "ion reservoir" and rolled-up metallic nanomembranes as the "soft contact." [300] As demonstrated in Figure 14H [281] Copyright 2010, American Chemical Society. B) Schematic and SEM image of outer rolled-up soft contact.…”
Section: Rolled-up Soft Contactmentioning
confidence: 96%
“…Design and microfabrication of the molecular devices. [Reproduced with permission from ref . Copyright 2022, Nature Publications.)…”
Section: Ooc Materialsmentioning
confidence: 99%
“…The AZ 5214E photoresist has been applied in the fabrication of micropattern of quantum dots, 14 chromium photomasks, 15 ultrabroadband infrared light absorber, 16 magnetoresistive sensing element, 17 needle-shaped ultrathin piezoelectric microsystem, 18 electronic skin 19 and integrated molecular devices. 20 UV optical lithography [14][15][16][17]19 is often adopted for lithography of AZ 5214E photoresist, but the fabricated structures depend on the prefabricated photomasks, which can not only increase the cost but also limit the flexibility for the fabrication of diverse micro/nanostructures. Skriniarova et al have reported the maskless lithography of AZ 5214E photoresist by using the laser interference, e-beam direct write lithography and near-field scanning optical microscopy lithography.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used as a positive photoresist, and can also be reversed as a negative photoresist through the additional reversal bake and flood exposure. The AZ 5214E photoresist has been applied in the fabrication of micropattern of quantum dots, 14 chromium photomasks, 15 ultrabroadband infrared light absorber, 16 magnetoresistive sensing element, 17 needle-shaped ultrathin piezoelectric microsystem, 18 electronic skin 19 and integrated molecular devices 20 …”
Section: Introductionmentioning
confidence: 99%